Comparative Study of One Dimensional and Two Dimensional Steady Surface Flow Analysis - Maharjan, Laxmi Bhakta; Shakya, Narendra Man (Journal of Advanced College of Engineering and Management, 2016)
Determination of actual water surface is required for design of hydraulic structures, reservoirs, flood plain management, and flood forecasting. Classical approach of analyzing the river flow using one dimensional flow analysis cannot provide the accurate information of water surface for different return period floods. So, both 1D and 2D steady surface flow analysis in prismatic channel and non-prismatic channel were done using models like HEC-RAS, FESWMS-2DH, GIS, and HECGEORAS to compare the results and recommended to select the best among these two flow analyses. Analysis of result showed that in prismatic channel, the water surface elevations obtained from 1D and 2D steady flow analysis for discharge Q=10cft/s were almost similar with maximum variation of 0.33ft. But in case of non-prismatic channel, the results of water surface elevations from 1D and 2D steady flow analysis for discharge Q = 5000cft/s and 9430cft/s were not similar and the maximum variation of 1.36ft and 1.75ft were found for two discharges respectively. 1D steady flow analysis is acceptable for prismatic channel except at bend which may require 2D analysis. But flow in non-prismatic channel requires 2D steady flow analysis for precise water surface elevation. Journal of Advanced College of Engineering and Management, Vol. 2, 2016, Page: 15-30